2012
DOI: 10.1530/rep-11-0192
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin in ovarian follicular development and ovulation in mammals: a review of recent advances

Abstract: Angiotensin (Ang) II is widely known for its role in the control of systemic blood vessels. Moreover, Ang II acts on the vascular control of ovarian function, corpus luteum formation, and luteolysis. Over the past 10 years, our research group has been studying the new concept of the renin-angiotensin system (RAS) as an autocrine/paracrine factor regulating steroidogenesis and promoting different cellular responses in the ovary, beyond vascular function. We have developed and used different in vivo and in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 75 publications
1
32
0
4
Order By: Relevance
“…Nevertheless, previous studies in rabbit have demonstrated that Ang II can stimulate testosterone production in theca cells cultured in vitro and treated with hCG (FERAL et al, 1995). These differences are likely due to a specie-specific factors since the RAS system is not uniform in mammals (GONÇALVES et al, 2012). In bovine, there was no effect of Ang II alone or in association with LH on androstenedione or testosterone synthesis in theca cells, neither on progesterone production induced by LH in granulosa cells (PORTELA et al, 2011).…”
Section: Resultsmentioning
confidence: 83%
“…Nevertheless, previous studies in rabbit have demonstrated that Ang II can stimulate testosterone production in theca cells cultured in vitro and treated with hCG (FERAL et al, 1995). These differences are likely due to a specie-specific factors since the RAS system is not uniform in mammals (GONÇALVES et al, 2012). In bovine, there was no effect of Ang II alone or in association with LH on androstenedione or testosterone synthesis in theca cells, neither on progesterone production induced by LH in granulosa cells (PORTELA et al, 2011).…”
Section: Resultsmentioning
confidence: 83%
“…8,9,39 One potential mechanism is direct activation of the renin-angiotensin system with ovarian hyperstimulation, [13][14][15] which influences systemic vascular permeability, sodium balance and blood pressure. 16 Fluid shifts may result in depletion of intravascular volume and interstitial edema that mediates ischemic stroke, heart failure and venothromboembolic risks during pregnancy and potentially thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fertility therapy may lead to adverse cardiovascular events by inducing background thrombosis, activating the renin-angiotensin system or inducing vascular injury from ovarian hyperstimulation. [8][9][10][11][12][13][14][15][16] The last mechanism may be further exacerbated in patients who undergo multiple cycles of fertility therapy or experience pregnancy miscarriages. [17][18][19][20][21] An association between fertility therapy failure and longterm cardiovascular risk could provide insight into nontraditional risk factors potentially contributing to the stagnation in the reduction of cardiovascular mortality observed among young women.…”
mentioning
confidence: 99%
“…Receptores AT 1 e AT 2 foram detectados em células da granulosa de folículos primordial, primário e secundários 17 . A Angiotensina II e seus receptores AT 1 e AT 2 parecem exercer efeitos reguladores no ovário em relação à maturação do núcleo do oócito e à ovulação em mulheres 18 . Além disso, folículos com elevada atividade SRA local foram associados com melhor qualidade do ovócito e aumento nas concentrações de fatores de crescimento vascular endotelial durante os procedimentos de fertilização in vitro 19 .…”
Section: Discussionunclassified